2017
DOI: 10.1038/cddis.2017.75
|View full text |Cite|
|
Sign up to set email alerts
|

miR-377 induces senescence in human skin fibroblasts by targeting DNA methyltransferase 1

Abstract: Skin aging is a complicated physiological process and epigenetic feature, including microRNA-mediated regulation and DNA methylation, have been shown to contribute to this process. DNA methylation is regulated by DNA methyltransferase, of which DNA methyltransferase 1 (DNMT1) is the most abundantly known. But evidence supporting its role in skin aging remains scarce, and no report regards its specifical upstream-regulating molecules in the process of skin aging so far. Here, we found that DNMT1 expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 49 publications
3
28
0
Order By: Relevance
“…Recently, 2 publications showed that miR-377 modulated senescence in human skin fibroblasts and reversed cancerous phenotypes of pancreatic cells through inhibiting DNMT1. 31,32 Consistently, our study revealed that miR-377 contained 8 bases that were predicted to complementary pair with DNMT1 UTR. Consistently, miR-377 directly targeted DNMT1 3'-UTR and suppressed its expression and activity.…”
Section: Mir-377 Reduces Triglyceride Levels Through the Dnmt1-gpihbpsupporting
confidence: 79%
“…Recently, 2 publications showed that miR-377 modulated senescence in human skin fibroblasts and reversed cancerous phenotypes of pancreatic cells through inhibiting DNMT1. 31,32 Consistently, our study revealed that miR-377 contained 8 bases that were predicted to complementary pair with DNMT1 UTR. Consistently, miR-377 directly targeted DNMT1 3'-UTR and suppressed its expression and activity.…”
Section: Mir-377 Reduces Triglyceride Levels Through the Dnmt1-gpihbpsupporting
confidence: 79%
“…Particularly in untreated skin, this increase was striking, because normal epidermis displayed no detectable p16Ink4a expression, as observed also by others (21). Also the reduction of DNMT1 protein can be considered as a senescence marker as DNMT1 protein is decreased in senescent fibroblasts (11,22,23) and mouse keratinocytes (as previously discussed). Moreover, the inhibition of DNMT1 promotes senescence in these cells (11, 22, 23, s.a.).…”
Section: Discussionsupporting
confidence: 67%
“…The authors found miR-290 to be responsible, in a Rbl2-dependent manner, of this transcriptional silencing (Benetti et al, 2008). Moreover, miR-377 represses DNMT1 and induces senescence in human skin fibroblasts (Xie et al, 2017).…”
Section: Epigenetic Changes and Chromatin Structurementioning
confidence: 97%